The Relationship Between Shyness and Interpersonal Communication Anxiety Among First-Year Students of the Faculty of Psychology at Universitas Medan Area - Ribcha Nigia Nawuazitarry Duha; Sabrini Mentari Rezeki; Rina Mirza; Zefanya Natasya Jouma Manalu; Tania Rosani Simanjorang (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
This study investigated the relationship between shyness and interpersonal communication anxiety among first-year students at the Faculty of Psychology, Universitas Medan Area. Employing a quantitative approach with a correlational design, sample were collected using a disproportionate stratified random sampling technique. The researchpopulation comprised 311 students, fromwhom a sample of 167 participants was drawn. The research instruments included two scales: an InterpersonalCommunication Anxiety Scale consistingof 65 statements (reliability of 0.745) anda Shyness Scale also with 61 statements(reliability of 0.741). Data analysis utilizing Pearson's product-moment correlation yielded an rxy value of 0.828 with a significance level of p < 0.05 (0.000). These findings indicate a significant positive relationship between shyness and interpersonal communication anxiety among first- year students at Universitas Medan Area, thus supporting the study's hypothesis.